Analysis of putative G-quadruplex forming sequences in inflammatory mediators and their potential as targets for treating inflammatory disorders. (June 2021) - Bidula, Stefan
Abstract: G-quadruplexes (G4s) are non-canonical secondary structures located in DNA and RNA which have demonstrable roles in the regulation of transcription and translation. G4s have received considerable interest as a drug target in cancer, given their ability to regulate the expression of proto-oncogenes and inhibit growth of cancer cells. However, their presence in the genes of inflammatory mediators has not been discussed to date. Therefore, we computationally investigated putative quadruplex-forming sequences (PQS) in the promoters and gene bodies of cytokines and chemokines. Here, we demonstrated that the promoters of IL-6, IL-12, IL-17, TGF-β, TNF, and β-chain family cytokines and XC and TAFA family chemokines display high PQS frequencies comparable to those observed in proto-oncogenes. Moreover, 47.82% of the gene promoters contained sequences with high propensity to form G4s. Furthermore, G4s can primarily be found within the GC-boxes and binding sites for specificity protein and Krϋppel-like transcription factors. However, they can also be found located in a further 59 sites involved in the binding of transcription factors involved in inflammation and immunity such as NF-κB1, RelA, RelB, IRF5, and NFAT5. We also identified that 72.17% and 70.43% of genes investigated contained sequences highly likely to form G4s in their coding and template strands, respectively. Exploring the regulatory roles of G4s in genes encoding inflammatory mediators could provide novel drug targets to modulate inflammation and treat inflammatory diseases.